(untitled) (Research, Society and Development, 2022)
Currently, vitamin D deficiency has been recognized as a pandemic caused by multiple factors. An increasing number of academics have focused their efforts on research related to the adverse effects of vitamin D deficiency and its possible association with pathologies, such as asthma. Few studies have been published with direct assessments of the role of vitamin D in asthma, but there is research that indirectly links this vitamin with disease mechanisms. This manuscript is an integrative review that used the PICO method (population, intervention, comparison, result) for the following question: “Does vitamin D supplementation help with asthma control?” Included in the study population were asthmatics, without other comorbidities; the intervention was supplementation with vitamin D and the comparison with non-supplemented individuals, the result analyzed was whether or not there was improvement in asthma control. In conclusion, high doses of vitamin D supplementation, associated with standard asthma treatment, can improve disease control parameters, although more studies are needed on the subject.